2010
DOI: 10.1111/j.1751-1097.2010.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB is Not Directly Responsible for Photoresistance Induced by Fractionated Light Delivery in HT‐29 Colon Adenocarcinoma Cells

Abstract: Our recent study follows up an earlier one which demonstrated hypericin-mediated photocytotoxic effects on HT-29 adenocarcinoma cells by light fractionation with a longer dark pause between two unequal light doses (Sackova, A. [2005] Photochem. Photobiol.81, 1411-1416). Here, we present closer study on events invoked by sublethal light dose (1 J cm(-2)) during the period of 6 h that is sufficient to invoke resistance to second lethal dose (11 J cm(-2)). First, we proved that the dark pause of 6 h, but not 1 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
0
13
0
2
Order By: Relevance
“…However, PDT could induce the activation of nuclear factor-kappa B (NF-κB) [8,9,10]. Several studies have indicated that NF-κB activation plays a negative role in PDT.…”
Section: Introductionmentioning
confidence: 99%
“…However, PDT could induce the activation of nuclear factor-kappa B (NF-κB) [8,9,10]. Several studies have indicated that NF-κB activation plays a negative role in PDT.…”
Section: Introductionmentioning
confidence: 99%
“…However, the light-independent action of HY generally requires markedly higher doses. The significance of proper light regime has also been suggested by us (Kuliková et al, 2010;Sačková et al, 2005) and it is now beyond doubt that low light doses induce photo-tolerance. Discontinuity time proved to be crucial.…”
Section: Hypericinmentioning
confidence: 99%
“…The main advantage of this approach is the combination of three inoffensive entities which together create a highly toxic conjunction, and so it has also found applications in the treatment of a wide range of malignancies (Ledo & Ledo, 2000). By its nature, PDT is a flexible and versatile therapeutic approach depending on the nature of the photosensitive compound, its concentration and incubation time, on the wavelength of light radiation, fluence rate and light dose, the time between drug administration and its activation (Kuliková et al, 2010), as well as on the histological origin of tissue and the oxygen pressure in it (Agostinis et al, 2002). All these factors modulate three independent processes contributing to tumour destruction by PDT: direct cell death, destruction of tumour vasculature causing tumour ischemia, and activation of an immune response (Buytaert et al, 2007).…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…O aumento da expressão de NFB em células sobreviventes tratadas com PDT já foi descrito em outros estudos com outras linhagens celulares e protocolos diversos de tratamento (Matroule et al, 2001;Kuliková et al, 2010). Em geral os autores concluem que o NFB desempenha um papel de proteção contra a apoptose induzida pela PDT, sendo responsável por vários mecanismos de resistência a essa terapia.…”
Section: Gruposunclassified
“…Os estudos demonstram ativação de vias celulares relacionadas à sobrevivência celular, ou seja, que promovem evasão da apoptose e proliferação celular. Por exemplo, menção tem sido feita à superexpressão de Akt (Song et al, 2013), NFB (Kuliková et al, 2010), iNOS Girotti, 2013) e proteína anti-apoptótica Bcl-2 (Shen et al, 2005) Não há relatos na literatura do desenvolvimento de células de CEC bucal resistentes a PDT, nem tampouco quando a PDT é mediada pelo ácido 5-aminolevulínico (5-ALA) nesses tumores. Esse FS tem sido utilizado para casos de lesões potencialmente malignais na cavidade bucal (Chen et al, 2005;Tsai et al, 2004), bem como para carcinomas verrucosos e CEC pouco invasivos Fan et al, 1996).…”
Section: Introductionunclassified